2010
DOI: 10.1097/scs.0b013e3181cf6084
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Alveolar Bone Grafting

Abstract: Management of alveolar cleft has dramatically changed during the last century: secondary alveolar bone grafting is now an integral part of cleft palate and craniofacial center's protocols. The objectives of alveolar repair and bone grafting are as follows: providing a continuous and stable maxillary dental arch, closure of oronasal fistulae, adequate bone for tooth eruption or orthodontic movement, and nasal base support, improving facial aesthetic. Although cancellous iliac bone is the donor site selected mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…There have been numerous attempts to avoid the iliac crest donor site for graft harvest. Alternate autograft donor sites have been proposed, 4446 but in our dataset, 97% of surgeons still favored the iliac crest as the optimal source of autograft. One of the potentially greatest changes in bone graft practices in recent years has been the introduction of numerous alternatives for the use of autograft.…”
Section: Discussionmentioning
confidence: 86%
“…There have been numerous attempts to avoid the iliac crest donor site for graft harvest. Alternate autograft donor sites have been proposed, 4446 but in our dataset, 97% of surgeons still favored the iliac crest as the optimal source of autograft. One of the potentially greatest changes in bone graft practices in recent years has been the introduction of numerous alternatives for the use of autograft.…”
Section: Discussionmentioning
confidence: 86%
“…These results indicate that Notch1 signals play a role in ABD repair, and PRF + BMSCs composites can more effectively promote the activation of the Notch1 signaling pathway (22). As a member of the Wnt signaling pathway family, Wnt3a signaling protein is a cysteine-rich secreted glucoprotein that binds to receptors on adjacent cell membranes through paracrine or autocrine action to activate signals at all levels in cells, regulates the related genes and the proliferation and differentiation of target cells (23). It was found that Wnt3a in rabbits in the combination group was greatly higher based on that in the PRF group and BMSC group at 5 and 10 weeks after surgery, showing statistically great differences (P<0.05), suggesting that the Wnt signaling pathway played a regulatory role in ABD repair.…”
Section: Discussionmentioning
confidence: 89%
“… 9 , 12 , 14 Furthermore, the OP has gained support among maxillofacial surgeons as an effective structural graft source with few and transient donor-site complications, including wound seroma and forearm paresthesias. 19 , 21 , 22 , 27 …”
Section: Discussionmentioning
confidence: 99%